DETERMINASI KOMPETENSI MAHASISWA MELALUI PENGALAMAN MAGANG DAN SOFT SKILLS - Efa Irdhayanti (Creative Research Management Journal, 2025)
His study aims to examine the effects of internship experience and soft skills on the competence of young people in Pontianak, with self-confidence as a moderating variable. A quantitative approach with a survey method was employed. Data were collected using a five-point Likert-scale questionnaire from 200 students and young graduates who had participated in internship programs in Pontianak. A purposive sampling technique was applied, targeting respondents aged 18–24 years who had prior internship experience in business and industrial settings. Data analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS software. The results indicate that internship experience and soft skills have a positive and significant effect on student competence. Self-confidence shows a positive but insignificant effect on competence and does not moderate the relationship between internship experience or soft skills and competence. This study is limited to respondents in Pontianak and employs a cross-sectional design, which restricts the ability to capture long-term competency development. This study highlights internship experience and soft skills as the main determinants of student competence and provides practical implications for internship-based curriculum development and soft skills enhancement in higher education.